Exploring the Path of Integrating Sports Psychology Education into College Physical Education Teaching - Kai Chuan; Hao Liu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In order to explore the path of integrating sports psychology education into physical education teaching in universities. The author takes undergraduate students from A Normal University in B city as the research object, and takes the physical exercise habits and mental health status of the research object as the research content. 1131 undergraduate students from Normal University were surveyed using the "Questionnaire on Exercise Habits of College Students" and the Symptom Checklist 90 (SCL-90).According to the criteria for judging whether it is a sports population, that is, the frequency of participating in physical exercise weeks is greater than or equal to 3 times, lasting for more than 30 minutes each time, and the exercise load is greater than or equal to medium based on one's own physical fitness and the sports activities performed. The strongest impact is on the mutual influence between "exercise effectiveness" and "somatization", followed by "exercise behavior" and "depression", while the non-impact is on the relationship between "thinking mode" and "fear", "paranoia", and "psychosis". Students with good "exercise behavior" and "exercise effect" have a certain degree of good mental health, among them, the improvement of depression is the most significant. Students with good mental health have significantly better physical exercise habits in terms of "exercise behavior" and "exercise effect", and "compulsion" has the greatest impact on "exercise behavior".